2015
DOI: 10.1080/10826068.2014.940539
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Intracellular Product Release fromNeisseria denitrificansUsing Microfluidizer

Abstract: Disruption of Neisseria denitrificans cells by microfluidizer was optimized using a factorial experiments design. The pH, pretreatment time, cell concentration, NaCl, ethylenediamine tetraacetic acid (EDTA) and Triton X-100 concentrations showed significant impact on disruption process and the process was optimized using central composite design and response surface methodology (RSM). Investigation revealed optimum conditions: 90 min pretreatment at pH 9.0 containing 110 g L(-1) cells (dry cell weight), 50 mM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, only at phase 4, a reduction from 10 to 30% of total protein content is observed when the permanent deformation is achieved. We believe that the stability of protein at high pressure and cycle is supported by the operative choice to perform the process under mild pressure conditions keeping the temperature in a range of 5–10 °C, as reported by several studies in different fields [ 31 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…However, only at phase 4, a reduction from 10 to 30% of total protein content is observed when the permanent deformation is achieved. We believe that the stability of protein at high pressure and cycle is supported by the operative choice to perform the process under mild pressure conditions keeping the temperature in a range of 5–10 °C, as reported by several studies in different fields [ 31 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 82%
“…This HPH works in a turbulent flow situation, thus inducing very high shear forces on the fluid sample in the interaction chamber. However, to date, biological applications of HPH are only aimed at cell lysis for the extraction of proteins or lipids of interest [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…(Li et al, 1997) and Alu I 250 ( Paenibacillus curdlanolyticus ) (Schoina et al, 2011), bacteria involved in N cycle including Alu I 228 ( Moorella thermoacetica ) (Silaghi-Dumitrescu et al, 2003), in nitrification, Hae II 331 ( Nitrospira ) (Dionisi et al, 2002), bacteria linked to pathogenicity, Msp I 538 ( Spiroplasma ) (Tully et al, 1977) and Hae III 209 ( Staphylococcus kloosii ) (Peer et al, 2011), and those of unknown function including Alu I 282 ( Haemophilus ), Alu I 229 ( Aquifex pyrophilus ), Msp I 538 ( Spiroplasma ) (Supplementary Table S1). The bacteria identified in NT soil included the S cycle bacteria, Msp I 74 ( Desulfohalobium retbaense ) (Ollivier et al, 1991), denitrification bacteria, Msp I 88 ( Neisseria denitrificans) (Stupak et al, 2015), mosquito eradication bacteria, Hae III 308 ( Bacillus sphaericus ) (Myers and Yousten, 1978), the C cycle bacteria including Hae III 338 ( Weissella ) (Choi et al, 2002), Alu I 232 ( Lactobacillus ) (Cheng et al, 1991) and bacteria associated with pathogenicity are Hae III 310 ( Staphylococcus ) (Lowy, 1998), Msp I 148 ( Aerococcus urinae ) (Aguirre and Collins, 1992), Afa I 100 ( Mycoplasma corogypsi ) (Wettere et al, 2013), Afa I 106 ( Mycoplasma neurolyticum ) (Aleu and Thomas, 1966), and Alu I 243 ( Mobiluncus curtisii ) (Meltzer et al, 2008) (Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Microfluidization techniques help to produce various nanodelivery systems including SLNs, nanoemulsions, nanoliposomes, and PLGA nanoparticles loaded with drugs or plant bioactive compounds with enhanced stability and bioavailability of those loaded compounds. [132][133][134][135][136][137][138][139] Various in vitro or in vivo studies have confirmed that these microfluidized nanodelivery systems loaded with bioactive compounds showed enhanced protection in the treatment of chronic diseases including cancer, obesity, neurological diseases, and diabetes. A few of those studies are discussed in the following sections.…”
Section: Role Of Microfluidized Nanodelivery Systems Loaded With Planmentioning
confidence: 95%